Integrating vulture social behavior into conservation practice. (26th August 2020) - van Overveld, Thijs; Blanco, Guillermo; Moleón, Marcos; Margalida, Antoni; Sánchez-Zapata, José Antonio; de la Riva, Manuel; Donázar, José Antonio
Abstract: Vultures are one of the most threatened bird groups globally. Although many of the threats faced by vultures have been identified, the impact of human activities on the social life of vultures has received little attention. In this paper, we emphasize the need to integrate vulture sociality into conservation practice. First, we summarize current knowledge on vulture social behavior, and the evolutionary and ecological roots of their breeding systems. We describe the existence of contrasting gradients in social foraging strategies and hierarchical social structures among colonial and territorial breeders associated with species (and population) reliance on carrion differing in size and predictability. We also highlight the potential role of vulture gatherings in maintaining population-level social structures and for mate-finding given high mate-selectivity. Next, based on this social framework, we discuss the impact of human activities on social foraging, territory structures, resource partitioning processes, and mating dynamics. However, little is known about how disruptions of social habits may have contributed to vulture population declines and/or may impede their recovery. Lastly, we provide directions for future research on vulture socio-ecology that may improve current conservation efforts. We encourage researchers and wildlife managers to pay more attention to natural carrion diversity underlying vulture social system diversity, especially when implementing supplementary feeding programs, and to consider the complex mating and settlement dynamics in reintroduction programs. Overall, we stress that understanding the complex social life of vultures is critical to harmonize their conservation with anthropogenic activities. Lay Summary: Although many of the threats faced by vultures have been identified, the impact of human activities on the social life of vultures has received little attention. We provide a comprehensive review of current knowledge of vulture social behavior and the evolutionary and ecological roots of their social systems. Within this social framework, we discuss aspects as diverse as vulture breeding and mating systems, foraging techniques, social hierarchies, territorial and gathering behavior, and interspecific interactions. Overall, we stress that advancing our socio-ecological understanding of the rich social life of vultures is critical to harmonize their conservation in this rapidly changing world. Graphical Abstract: